Public Policy Analysis: Root Causes and Solutions of Sexual Violence in Aceh - Aulia Putri Rezky; Febriana Andiani Putri (Program Pascasarjana Universitas Negeri Makassar, 2024)
This paper aims to analyze the problem of sexual violence in Aceh using the Multiple Perspective Analysis theory introduced by William N Dunn. Sexual violence is complex problem with cases like an iceberg phenomenon where few cases are visible or openly reported while the majority of the problem remains hidden or undetected. Sexual violence cases in Indonesia are difficult to handle in many provinces, such as Aceh, where this problem has been a protracted problem that must be resolved with effective solutions. The method used in this paper is a qualitative method with secondary data sources and literature studies. The results found by the researcher show that the problem of sexual violence in Aceh caused by multiple factors ranging lack of availability for safe house facilities and the unoptimal service system from the PPA unit at Aceh police, TPKS Law that cannot be implemented optimally due to overlapping regulations with Qanun Jinayat, and the taboo discussion of “sex” in the community that impacts survivors who often get negative stigma from the community. This research provides useful implications for a sustainable sexual violence response system in Aceh that requires effective leadership from the government, efficient infrastructure, and an effective response system.